Assessment of soil quality indicators on different slope aspects in Duhok’s highlands (Kurdistan region – Iraq). - Ameen, Hajar Ameen; Salem, Salar Mohammad Ameen (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study was conducted to assess the influence of slope aspect on some physical, chemical and biological indicators of soil quality in Mountain in Brifka village that located at about 20 km east of Duhok province in Iraqi Kurdistan region, having the same climatic, and vegetation. Soil samples were collected randomly and at uniform intervals along north and south facing slopes aspect. The soil quality has been represented by some physical, chemical and biological indicators such as: soil texture, bulk density, moisture content, organic carbon, pH, electrical conductivity, soil basal respiration, microbial biomass C, potentially mineralizable N and metabolic quotient. The results indicated that, except in few cases, the majority of studied soil quality indicators were significantly affected by slope aspect. The mount of soil moisture content, silt mineral fraction, soil organic C, soil basal respiration, microbial biomass was significantly higher in north facing slope compared to south facing slope, while sand fraction and bulk density were significant higher on south aspect than north aspect. No significant differences were found in clay fraction, soil pH, electrical conductivity, potentially mineralizable N and metabolic content. It was suggested that the slope aspect has effects on soil quality indicators and for better rangeland and landscape management it is very important to take the topographic aspect into consideration.
Keywords: Slope aspect,microclimate; soilquality indicators,microbial biomass